Secondary Bacterial Infections Associated with Influenza Pandemics - Morris, Denise E.; Cleary, David W.; Clarke, Stuart C. (Frontiers in Microbiology, 2017)
Lower and upper respiratory infections are the fourth highest cause of global mortality (Lozano et al., 2012). Epidemic and pandemic outbreaks of respiratory infection are a major medical concern, often causing considerable disease and a high death toll, typically over a relatively short period of time. Influenza is a major cause of epidemic and pandemic infection. Bacterial co/secondary infection further increases morbidity and mortality of influenza infection, with Streptococcus pneumoniae, Haemophilus influenzae and Staphylococcus aureus reported as the most common causes. With increased antibiotic resistance and vaccine evasion it is important to monitor the epidemiology of pathogens in circulation to inform clinical treatment and development, particularly in the setting of an influenza epidemic/pandemic.